2018
DOI: 10.1002/1873-3468.12986
|View full text |Cite
|
Sign up to set email alerts
|

ARRDC3 suppresses colorectal cancer progression through destabilizing the oncoprotein YAP

Abstract: Although colorectal cancer (CRC) is a prevalent malignancy of the digestive system, the underlying mechanisms of CRC tumorigenesis are still elusive. Arrestin-related domain-containing protein-3 (ARRDC3) has been reported to promote lysosome-mediated protein degradation. In the present study, we find that the expression of ARRDC3 is downregulated in CRC specimens. Mechanistically, we reveal that ARRDC3 binds and decreases expression of the oncoprotein YAP, the cotranscription factor of the Hippo pathway. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…In patient samples and in preclinical Drosophila models, Arrestin-related domain-containing protein-3 (ARRDC3) was downregulated in the colorectal cancer specimens. ARRDC3 promoted YAP degradation, increased drug sensitivity of the tumor cells and was proposed as a potential drug target (Shen et al, 2018). In another study, loss of Mst1/2 or conditional overexpression of YAP in response to bile acid induced injury in liver cells was shown to cause Hepatocellular carcinoma (HCC) in mice models.…”
Section: Oncogenic Cooperation-models For Cell–cell Interactions Tummentioning
confidence: 99%
“…In patient samples and in preclinical Drosophila models, Arrestin-related domain-containing protein-3 (ARRDC3) was downregulated in the colorectal cancer specimens. ARRDC3 promoted YAP degradation, increased drug sensitivity of the tumor cells and was proposed as a potential drug target (Shen et al, 2018). In another study, loss of Mst1/2 or conditional overexpression of YAP in response to bile acid induced injury in liver cells was shown to cause Hepatocellular carcinoma (HCC) in mice models.…”
Section: Oncogenic Cooperation-models For Cell–cell Interactions Tummentioning
confidence: 99%
“…Down-expression of ARRDC3 was first observed in breast cancer, and aberrant expression of ARRDC3 was correspondingly observed in multiple malignant tumors, including renal cell carcinoma, prostate cancer, cervical cancer, and colorectal cancer. [14][15][16] Given previous studies on ARRDC3 in tumors, therefore, we launched a study aiming to detect a correlation between ARRDC3 and OC.…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous reports have reported that the expression of ARRDC3 is associated with various diseases, including inflammatory disease and malignant tumors. [12][13][14][15][16]26 However, information relating to the association between ARRDC3 and OC remained unknown.…”
mentioning
confidence: 99%
“…In support of this model, bafilomycin, an inhibitor of lysosomal acidification, increased Yki activity and reversed the effect of Leash over expression. A recent study has confirmed the corresponding Arrdc3-Yap1 interaction in human cells (Shen et al, 2018). Intriguingly, the authors of the Leash study also found that overexpression of Wts could increase the abundance of Yki-positive vesicles in cultured cells, prompting the hypothesis that Yki endolysosomal trafficking may be regulated by the canonical Hippo pathway, rather than operating in parallel to it.…”
Section: Leashmentioning
confidence: 84%